CLINICAL PROFILE AND OUTCOME OF VENTILATED CHILDREN IN A PEDIATRIC INTENSIVE CARE UNIT OF A TERTIARY CARE HOSPITAL - Muhammad Sulman Javaid (Army Medical College Rawalpindi, 2020)
Objective: To assess the clinical profile and outcome of mechanically ventilated patients at a pediatric intensive care unit of a tertiary care teaching hospital of Pakistan.